Laura's star - de Rycker, Piet.; Rothkirch, Thilo Graf.; Madel, Michael; Lindner, Alexander; Warner Bros.; Rothkirch Cartoon-Film Production; Warner Bros. Film Productions Germany; Warner Home Video (Phils.). (Burbank, Calif. Warner Home Video ; distributed in the Philippines by Warner Home Video (Phils.), 2005)
Laura is new to the neighborhood, and more than a little homesick. But then she rescues a fallen star who's homesick too ... and shares a friendship that turns her strange new surroundings into a wonderful new place called home.
Based on the books by Klaus Baumgart published by Baumhaus Verlag.
Originally released as a motion picture in 2004.
Directors of animation, Kris Van Alphen, Alberto Campos ; art director, Alexander Lindner ; music, Hans Zimmer, Nick Glennie-Smith ; title song, Wonderwall ; production designer, Man Arenas.
Voices: Clemmie Hooton, Anthony Da Silva, Matthew Thomas-Davies.
VCD
Keywords: Animated films; Children's films; Drama